Designing a Mobile Serious Game for Raising Awareness of Diabetic Children - Alaa Mohammed Moosa (16864248) (2020)
Mobile serious games are very important tools for self-learning, training, and edutainment. They can be used to improve the children's learning skills to grasp new concepts rapidly in an enjoyable manner. Fun, motivation, and engagement are the most important features in designing attractive serious games. Therefore, designers should always find the best strategies and techniques to keep children playing the game with motivation and enthusiasm. The process is very long and requires different expertise from all the stakeholders. Arcade games are the most played games for fun and amusement in the last decades. Their approach is based on simplicity, easiness, repetitiveness, and soft challenges. The players of arcade games need only to improve their scores in every episode and avoid frustration and hard challenges as in other games. Hence, this arcade-based approach can be used in designing attractive serious games for young children and adolescents. We propose in this research a new serious game for diabetic children to teach them about the disease in a very easy manner. The game uses the arcade approach coupled with useful information about diabetes where the children discover them incrementally during the play. The longer time the child spends on the game, the most she/he can learn and enhance her/his knowledge on the disease. The game success came from its design and implementation with the presence of diabetes children, advisors, and nutritionists. We compare the game with the well-known DEX pet-based game for diabetes awareness on different aspects including user experience, usability, and learning outcomes. The study is conducted on twenty children from a diabetes camp who accepted voluntarily to participate in this research. We evaluate their educational aspects, using an improved version of the MEEGA+ model. We demonstrate the importance of the proposed game in enhancing the children knowledge on diabetes and adopt a new healthy lifestyle. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2020.3043840